The Experience of Being Born: A Natural Context for Learning to Suckle - Jeffrey R. Alberts; April E. Ronca (Hindawi Limited, 2012)
Understanding the developmental origins of congenital capabilities such as sucking is fundamental knowledge that can contribute to improving the clinical management of early feeding and facilitate the onset of oral ingestion. We describe analyses in rats showing that sensory stimulation in utero and during birth establishes the newborn's sucking responses to maternal cues. We mimicked elements of labor and delivery (viz., compressions simulating labor contractions, stroking simulating postnatal maternal licking of the newborn, and postnatal thermal flux), and used them to induce postnatal respiration and nipple attachment in caesarian-delivered pups. We report herein new data showing that, by simulating a fetal rat's experience of being born, specific components of vaginal birth provide sufficient conditions for the odor learning that guides newborn's sucking responses. In contrast, the absence of in utero compressions was associated with poor sucking onset. Knowing how birth stimuli contribute to the first nipple attachment and constitute a context for learning to suckle is an important step toward better management of some early feeding problems. It can serve also as a foundation for understanding the challenges of facilitating sucking by babies born prematurely so that they do not experience the typical contingencies mediating onset of oral ingestion.